Media critique in the age of Gillray : scratches, scraps, and spectres - Monteyne, Joseph (University of Toronto Press, 2022)
Dark Media and the Materiality of Nothing -- Haunted Media -- Good Copies, Bad Copies -- Social Detritus, Paper Detritus.